True knot at the time of delivery: electronic fetal monitoring characteristics and neonatal outcomes. (December 2018) - Carter, Ebony; Chu, Cheryl; Thompson, Zach; Tuuli, Methodius; Macones, George; Cahill, Alison
ABSTRACT Objective Determine the association between electronic fetal monitoring and neonatal outcomes in the setting of a true knot at delivery. Study design This was a planned secondary analysis of a prospective cohort of 8580 women. Patients with and without a true knot were compared and the primary outcome was repetitive late decelerations occurring with at least 50% of contractions. Confounders were adjusted for using logistic regression. Results A total of 8580 patients met inclusion criteria and 49 (0.57%) had a TK. There was no significant difference in the rate of repetitive late decelerations in patients with TK (aOR 1.04; 95% confidence interval [CI] 0.25–4.40), other electronic fetal monitoring parameters, or neonatal outcomes. Conclusion Neonates with true knots who are delivered at term have similar electronic fetal monitoring characteristics compared to those without true knots and no detectable difference in neonatal morbidity; thus, calling into question the clinical significance of a true knot at term.